Associação entre fatores de risco cardiovascular e capacidade funcional de idosos longevos - Dos Santos, Vanessa R. [UNESP]; Gomes, Igor C.; Dos Santos, Lionai L. [UNESP]; Agostinete, Ricardo R. [UNESP]; Freitas Jr., Ismael F. [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2013)
Study design: cross-sectional study. Objective: To assess the association between the presence of cardiovascular risk factor (CRP) and functional capacity of the oldest old. Methods: The sample 9onsisted of 91 elderly aged 80 and 90 years (83.0 ± 2.5 years) with 60 women (82.2 ± 2.1 years) and 31 men (83.2 ± 2,6 years) residing in the city of Presidente Prudente - SP. The FRC were analyzed: arterial hypertension (AH) and excess body fat (total and trunk). The presence of hypertension was verified by means of self-reported questionnaire based on the Standard Health Questionnaire (SHQ). Assessment of body was made by absorpiometria dual energy X-ray absorptiometry (DXA) and functional capacity was assessed by the functional tests (static balance, normal walking speed and force of the lower limbs). For statistical analysis we carried out the chi-square test, the software used was SPSS (13.0) and the significance level was set at 5%. Results. In males, with hypertension and the presence of excess %BF had lower performance in the lower limbs (83.3% lower and 16.7% higher), p = 0.011 compared to those with only a VCF. The elderly women with hypertension and the presence of excess GTron% also had lower performance on the same test (80.6% lower and 19.4% higher), p = 0.018 and the test of walking speed (80.6% lower and 19.4% higher), p = 0.034. Conclusion: Arterial hypertension and excess body fat (total and trunk) aggregated are FRC, which are associated with reduced functional capacity of the oldest old.
Association between cardiovascular risk factors and functional capacity of the oldest old
Keywords: Aged, 80 and over; Blood pressure, high; Body composition; Hypertension; Physical fitness; aged; body fat; cardiovascular risk; cross-sectional study; disease association; dual energy X ray absorptiometry; female; functional status; human; hypertension; major clinical study; male; questionnaire; walking speed